Tutorial: Graph-based Methods for Similarity Searches - Shimomura, Larissa C.; Kaster, Daniel S. (Anais Estendidos do Simpósio Brasileiro de Banco de Dados (SBBD), 2023)
Similarity searches are based on retrieving similar data of one or more data used as reference according to an intrinsic characteristic of the data. Recently, graph-based methods have emerged as a very efficient option to execute similarity queries in metric and non-metric spaces. Graphs model the interconnectivity among data, enabling us to explore relationships and neighbors in an agile way. In this tutorial, we will give an introduction to similarity searches and present graph-based methods for similarity searches, the types of graphs used in such methods, their properties, open challenges, and research opportunities.